Socio-economic mechanism of impact on the demographic processes at a micro-level - Яковенко, Р. В.; Yakovenko, R. (Kropyvnytskyy : Publications Unit of CUNTU, 2016)
This thesis discloses the problems of demographic development of present day Ukraine in their interrelation with the current economic situation. The author defines the levels and mechanism of socio-economic influence on demographic processes. Demographic functions of the main microeconomic categories “household” and “enterprise” were defined and a theoretically-methodological base for strengthening their role in the improvement of national demographic conditions was created. Тези розкривають проблематику демографічного розвитку сучасної України та її взаємозв’язок з економічним станом. Автор визначає рівні та механізм соціально-економічного впливу на демографічні процеси. Визначаються демографічні функції головних мікроекономічних категорій “домогосподарство” та “підприємство”, також створюється теоретико-методологічна база щодо посилення їхньої ролі в поліпшенні загальнодержавного демографічного стану.
Соціально-економічний механізм впливу на демографічні процеси на мікрорівні
Keywords: demographic processes; household; enterprise; micro-level; subjects of impact; демографічні процеси; домогосподарство; підприємство; мікрорівень; суб’єкти впливу